Evaluating the influence of light intensity in mcyA gene expression and microcystin production in toxic strains of Planktothrix agardhii and Microcystis aeruginosa - Salvador D. (2016)
Cyanobacteria are phytoplanktonic organisms widely occurring in freshwaters, being frequently associated with the production of toxins, namely microcystins (MCs). MCs are produced non-ribosomally by a multienzyme complex (mcy genes). It has been reported that environmental factors, such as light intensity, can influence toxin production. The aim of this study was to assess the influence of light intensity in the transcription of the mcyA gene and corresponding production of microcystins in toxic isolates of Planktothrix agardhii, where little is known, and compare them to Microcystis aeruginosa. For that purpose, cultures were exposed to three different light intensities (4, 20 and 30 μmol photons m-2 s-1) for 18 days at 20 ± 1 °C. The growth was followed daily using absorbance readings. Samples were collected at each growth stage for cell counting, microcystins quantification and RNA extraction. The level of transcripts was quantified by RT-qPCR and the relative expression determined using 16S rDNA, gltA and rpoC1 as reference genes. The most stable reference genes in M. aeruginosa were rpoC1 and gltA, whereas in P. agardhii were 16S rDNA and gltA. There was a correspondence between the growth rate and light intensity in M. aeruginosa and P. agardhii. The growth rates for both species were lower at 4 and higher at 30 μmol photons m-2 s-1. Microcystin concentration per cell was similar between light intensities in M. aeruginosa and over time, while in P. agardhii it was higher in the stationary phase at 4 μmol photons m-2 s-1. There were differences in the expression of mcyA between the two species. In M. aeruginosa, the highest levels of expression occurred at 4 μmol photons m-2 s-1 in the adaptation phase, whereas for P. agardhii it was at 4 μmol photons m-2 s-1 in the exponential growth phase. Our results indicate that the light intensities tested had distinct influences on the growth, microcystin production and mcyA expression levels, presenting considerable differences in M. aeruginosa and P. agardhii. © 2016 Elsevier